CONGENITAL TOXOPLASMOSIS Â€“ REPORT OF AN ATYPICAL CASE IN A PEDIATRIC PATIENT (CIPEEX, 2022)
INTRODUCTION: CONGENITAL TOXOPLASMOSIS CAN RESULT IN SERIOUS PROBLEMS FOR THE NEWBORN, ESPECIALLY IN THE BRAIN AND EYES. THE PROTOZOAN CAUSING THE DISEASE CROSSES THE PLACENTAL BARRIER IN ABOUT 40% OF CASES. IT IS EXTREMELY IMPORTANT TO PERFORM A COMPLETE PRENATAL CARE DURING PREGNANCY TO PREVENT FURTHER COMPLICATIONS TO THE FETUS RELATED TO TOXOPLASMOSIS. OBJECTIVE: TO REPORT A CASE OF CONGENITAL TOXOPLASMOSIS IN NEWBORNS WITH NEUROLOGICAL COMPLICATIONS, ANEMIA AND PNEUMONIA. CASE REPORT: 36-WEEK-OLD PATIENT, DIAGNOSIS OF CONGENITAL TOXOPLASMOSIS EVOLVED WITH CHRONIC NEUROPATHY, PNEUMONIA, AND ANEMIA. SHE WAS HOSPITALIZED IN THE ICU, RESPONDED WELL TO TREATMENT AND WAS DISCHARGED. FINAL CONSIDERATIONS: DESPITE INSUFFICIENT PRENATAL CARE PERFORMED BY THE MOTHER, THE PATIENT WAS ABLE TO BE FOLLOWED CLINICALLY IN TIME, RESPONDED WELL TO TREATMENT AND COULD BE CURED. IT IS ALSO EMPHASIZED THAT THE PRESENCE  OF CONGENITAL TOXOPLASMOSIS SHOULD ALWAYS BE CONSIDERED BEFORE THE PRESENCE OF THE SYMPTOMS REPORTED IN THIS STUDY, BECAUSE THE CONDITION DISORDER MAY, IN SOME PATIENTS, RAPIDLY EVOLVE TO DEATH
Keywords: toxoplasmosis; congenital; newborn